Analisis Fikih Muamalah terhadap Sistem Pengupahan Freelance “X” Wedding dan Event Organizer - Muhamad Farid Solehudin; Encep Abdul Rojak; Akhmad Yusup (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Service work in muamalah fiqh is included in the Ijarah Al-amal contract, in which the provisions must determine how much nominal wages will be given to workers. However, in "X" Wedding and Event Organizer, Sighat or statements of offer and acceptance/ al-ijab wa al-qabul are unclear, so it will have the potential to make the contract fasid or damaged. Based on these problems, the purpose of this research is to find out the remuneration system according to Islamic law, namely, Fiqh Muamalah, to find out the remuneration system for freelancers or workers who are not bound by a contract at "X" Management Wedding & Event Organizer, and to find out Muamalah Fiqh Analysis of the Freelance remuneration system at “X” Wedding & Event Organizer. The research method used is juridical-empirical, namely, field research that examines the legal provisions and normative rules that apply and what happens in reality in people's lives. The type of data consists of two types, namely literature data (Library Study) and field data (observation and interview results) with data analysis carried out qualitatively. The results of the study show that the wage system in Muamalah Jurisprudence Analysis must be determined by agreement between the two parties by carrying out the principle of justice, the wage system at "X" Wedding & Event Organizer is paid to Freelancers after the client has paid off payments to "X" Wedding & Event Management Organizer, and the wage system for freelancers or non-contractual workers carried out by "X" Wedding & Event Organizer is not fully in accordance with the provisions of Islamic law, namely fiqh muamalah. Keywords: Contract, Ijarah, and Wedding Organizer.. Abstrak. Pekerjaan jasa dalam fikih muamalah termasuk ke dalam akad Ijarah Al-amal, dimana ketentuannya harus ditentukan berapa nominal upah yang akan diberikan kepada para para pekerja. Akan tetapi pada “X” Wedding dan Event Organizer, Sighat atau pernyataan penawaran dan penerimaan/ al-ijab wa al-qabul yang tidak jelas, sehingga akan berpotensi membuat akad menjadi fasid atau rusak. Berdasarkan permasalahan tersebut, maka tujuan penelitian ini adalah mengetahui sistem pengupahan menurut Hukum Islam yakni Fikih Muamalah, mengetahui sistem pengupahan freelance atau pekerja yang tidak terikat kontrak pada “X” Management Wedding & Event Organizer, dan untuk mengetahui Analisis Fikih Muamalah terhadap sistem pengupahan Freelance pada “X” Wedding & Event Organizer. Metode penelitian yang digunakan adalah yuridis-empiris, yaitu penelitian lapangan yang mengkaji ketentuan hukum dan aturan normatif yang berlaku serta apa yang terjadi dalam kenyataan yang terjadi dalam kehidupan masyarakat. Jenis data terdiri dari dua jenis yaitu data literatur (Studi Pustaka) dan data lapangan (hasil observasi dan wawancara) dengan analisa data dilakukan secara kualitatif. Hasil penelitian menujukkan bahwa Sistem upah pada Analisis Fikih Muamalah harus ditentukan atas kesepakatan antara kedua belah pihak dengan menjalankan prinsip keadilan, sistem upah pada “X” Wedding & Event Organizer dibayarkan kepada para Freelance setelah pihak klien melunasi pembayaran kepada manajemen “X” Wedding & Event Organizer, dan Sistem pengupahan para Freelance atau pekerja tidak terikat kontrak yang dilakukan “X” Wedding & Event Organizer belum sepenuhnya sesuai dengan ketentuan Hukum Islam yakni fikih muamalah. Kata Kunci : Akad, Ijarah, dan Wedding Organizer..